Multi-proxy data set of the sediment core Co1410 from Lake Imandra, NW Russia - Lenz, Matthias; Savelieva, Larisa; Frolova, Larisa A; Cherezova, Anna; Moros, Matthias; Baumer, Marlene M; Gromig, Raphael; Kostromina, Natalia; Nigmatullin, Niyaz; Kolka, Vasili V; Wagner, B; Fedorov, Grigory B; et al. (PANGAEA, 2021)
The sediment succession of Lake Imandra in the central Kola region was investigated by a hydro-acoustic survey followed by sediment coring of site Co1410 (67°42'56.76"N, 33°5'6.42"E) down to the acoustic basement. We reconstructed the environmental history of Lake Imandra after the last deglaciation based on physical, biogeochemical, sedimentological, granulometrical, and micropalaeontological proxies. Our findings reveal the timing of the onset of lacustrine sediment deposition in the lake basin during the Late Glacial and the variability of climatic signals throughout the Holocene. All datasets comprise a depth and age column and: 1. S = Sulfur (%); TOC = Total Organic Content (%); TOC/TN = Total Organic Content / Total Nitrogen; Water Content (%); Grain Size d50 (µm); EM1 =Endmember 1 (%); EM2 =Endmember 2 (%); EM3 = Endmember 3 (%) 2. Acroperus harpae; Alona affinis; Alona guttata/Coronatella rectangula; Alona intermedia; Alona quadrangularis; Alona rustica; Alonella excisa; Alonella exigua; Alonella nana; Alonopsis elongata; Bosmina (Bosmina) longirostris; Bosmina (Eubosmina) cf. longispina/cf. coregoni; Chydorus cf. sphaericus; Daphnia longispina agg.; Eurycercus sp. Leptodora kindtii; Monospilus dispar; Paralona pigra; Pleuroxus truncatus; Rhynchotalona falcata; Planktonic; Littoral-benthic ; (%) Acroperus harpae; (%) Alona affinis; (%) Alona guttata/Coronatella rectangula; (%) Alona intermedia; (%) Alona quadrangularis; (%) Alona rustica; (%) Alonella excisa; (%) Alonella exigua; (%) Alonella nana; (%) Alonopsis elongata; (%) Bosmina (Bosmina) longirostris; (%) Bosmina (Eubosmina) cf. longispina/cf. coregoni; (%) Chydorus cf. sphaericus; (%) Daphnia longispina agg.; (%) Eurycercus sp.; (%) Leptodora kindtii; (%) Monospilus dispar; (%) Paralona pigra; (%) Pleuroxus truncatus; (%) Rhynchotalona falcata 3. magnetic susceptibility (SI * 10^-5) 4. Pinus(%); Artemisia (%); Total Pollen Concentration /1000; AP/NAP; Arboreale Pollen (%); Non-Arboreale Pollen (%) 5. Zr/Rb (log); Rb/Sr; Zr/Al; K/Al; Ti (cps); Ti/Al; Si (cps); Si/Ti; Br/Al; Fe (cps); Fe/Mn
Keywords: Anthropogenic impact; climate history; Glacial history; Kola region; Lake Imandra